Development of an experimental model for Anophryoides haemophila (Scuticociliatida: Orchitophryidae), a parasite of american lobster Homerus americanus - ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), F.; SPEARE, D.; CAWTHORN, R. J.; MacMILLAN, R.; DESPRES, B. (Journal of the Hellenic Veterinary Medical Society, 2017)
The principal lesions due to the ciliate Anophryoides haemophila in experimentally infected lobsters are observed in gills and connective tissue from the 9th week post-infection. These lesions were not related to the inoculum of parasites and were consistent in all inoculum studies (2,000, 10,000 and 500,000 ciliates per lobster) and were present in both euthanized and dead lobsters. The higher inocula resulted only in higher numbers of parasites observed in sections of gills and in the connective tissue of more organs, with no penetration to the parenchyma of any organ. Furthermore, the highest inoculum of ciliates (500,000 per lobster) resulted in a shorter course of disease development and consequendy, experimental lobsters died between 4th and 6th week post-infection. This was not observed at inocula of 2,000 and 10,000 ciliates per lobster, where mortality occurred 11-14 weeks post-infection.